Levels of handwashing and vaccine uptake in Kenya, Uganda, and Tanzania to prevent and control COVID-19: a systematic review and meta-analysis - Muchangi, Martin (Front. Public Health, 2023)
Introduction: Coronavirus Disease 2019 (COVID-19) presents a massive challenge in Africa due to overwhelmed and underresourced health systems, as well as the existing burden of communicable and non- communicable diseases. Self-inoculation may occur when an individual touches their mucous membrane following direct contact between their hands and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-contaminated surfaces. Therefore, handwashing can be used along with COVID-19 vaccines to reduce the spread of SARS-CoV-2 and the burden of COVID-19. We were interested in investigating the levels of handwashing and vaccine uptake to control and prevent COVID-19 in Kenya, Uganda and Tanzania using a systematic review and meta-analysis. Methods: We searched PubMed, African Index Medicus and African Journals Online for studies published since inception to 31st January 2023. We included all studies that assessed: the levels of COVID-19 vaccine acceptance and hesitance as indicators of vaccine uptake; and studies on the levels of handwashing to prevent and control COVID-19 in Kenya, Uganda and Tanzania. Study findings were synthesized by meta-analysis to get the pooled effect measure. Three studies were synthesized qualitatively due to high level of heterogeneity in effect measure precluding a quantitative meta-analysis. Results: Our search identified 128 articles of which 17 studies with 18,305 participants and 622 vaccination sites were reviewed with 14 of them being meta-analyzed. This systematic review and meta-analysis reports high levels of COVID-19 vaccine acceptance and handwashing in Kenya, Uganda and Tanzania at 67% (95% CI: 55, 78) and 88% (95% CI: 73, 97), respectively. Vaccine hesitance among the participants was low at 31% (95% CI: 15, 49). Discussion: Despite their importance in the control and prevention of COVID-19, some countries do not implement handwashing and vaccination effectively. There is a need for public health strategies to raise awareness about the importance of handwashing and the uptake of the COVID-19 vaccine.
Keywords: COVID-19; Kenya; Uganda; control; handwashing; policy; prevention; vaccine